E-007 Spontaneous post-partum cervical carotid artery dissection in a patient with reversible cerebral vasoconstriction syndrome. (12th July 2011) - Soltanolkotabi, M; Ansari, S; Shaibani, A; Singer, T; Hurley, M
Abstract : Postpartum cervicocephalic artery dissection (pp-CAD) is a rare and poorly understood condition. To our knowledge, only 21 cases have been reported. Reversible cerebral segmental vasoconstriction was first described by Call and Fleming in 1988, and its association with pp-CAD has only been reported in three cases. However, in those cases it is unclear whether the pp-CAD may have been caused by straining during labor and therefore merely coincidental to the intracranial arteriopathy. We report a 42-year-old right handed African-American woman who developed the syndrome of pp-CAD (headaches, trace sub-arachnoid hemorrhage and diffuse cerebral arteriopathy on angiogram) 2 weeks after delivery. In this unique case, the patient had fortuitously undergone an MR study twice over a 4-day period which included the carotid bifurcations. During that time the patient was an inpatient, on bed rest and subject to continuous cardiac monitoring. The interval studies documented a true spontaneous right internal carotid artery dissection occurring without obvious cause. The patient had noted moderate right neck pain developing between the two MR studies but experienced no neurological deficits. Subsequent conventional angiography confirmed the presence of postpartum cerebral arteriopathy and the cervical dissection. The patient was managed conservatively with antiplatelet medication and had an otherwise uneventful course. We hypothesize whether transient arterial wall abnormalities, postpartum hormonal changes or subtle connective tissue aberrations play a similar role in the pathogenesis of these two associated conditions.